Acute Oral Toxicity of Immunoglobulin Y (IgY) anti HIV in Mice - Sri Agus Sudjarwo, Wiwiek Indriyani, Nasronudin Nasronudin, Giftania Wardani Sudjarwo, Koerniasari Koerniasari (Journal of Applied Pharmaceutical Science, 2015)
The production of antibodies in chickens and the extraction of specific antibodies from egg yolk (IgY antibodies) are increasingly attracting the interest of the scientific community, as demonstrated by the significant growth of the IgY literature. The objective of the study was to evaluate the oral acute toxicity of IgY anti HIV on Mice. In acute toxicity study, mice by administering once orally graded doses of the IgY anti HIV in the ranges of 0.9375 g to 15g /kg body weight and observed for 14 days and the number of dead mice was recorded and used in the calculation of the acute toxicity value (LD50). The mice were also observed for other signs of toxicity, such as convulsion, diarrhea, cornea reflex, dyspnea, righting reflex, straub. Oral administration of IgY anti HIV at dose of 0.9375; 1.875; 3.75; 7.5; 15 g/kg body weight showed there no mortalities or evidence of toxicity effects, suggesting that the LD50 value of IgY anti HIV was more than 15000 mg/kg body weight. Throughout 14 days of the treatment no changes in behavioural pattern, clinical sign of toxicity, vital organs weight (liver, lung, heart, spleen and kidney) and body weight of mice in both control and treatment groups. Also there were no any significant alterations in the biochemical analysis of the blood serum (SGPT, SGOT, BUN and Creatinine).The overall finding of this study indicates that the oral administration of IgY anti HIV did not produce any significant toxic effect and practically non toxic in mice. Hence, the IgY anti HIV can be utilized for immunotherapy on HIV patient.
Keywords: Acute toxicity, IgY anti HIV, mice.